The role of the disciples in the Jesus story communicated by Mark - Hartin, Patrick (Koers, 1993)
This paper argues that the Gospels are to be taken seriously as communicative narratives. An attempt will be made to apply what scholars have presented under the study of narrative criticism to the Gospels themselves. In particular an attempt will be made to use the results of narrative criticism to gain an insight into the role that the character of the disciples as a group plays within the Gospel of Mark. The disciples are called to be 'the in siders’ to whom Jesus communicates the mystery of the kingdom. However, as the narrative progresses, the group of disciples is seen to change from that of ‘insiders’ to ‘outsiders’. Against this background of the development of the narrative it is argued that the much disputed ending of Mark 16:8 is highly appropriate to the entire narrative. The disciples have deserted Jesus out of fear. Concerned with themselves and their own ambitions, Jesus’ disciples are unable to appreciate Jesus’ teaching on the true nature of God ’s rule. The reader is challenged to avoid those failings of the disciples a n d to imitate Jesus' example.